Financial Feasibility Analysis of Tilapia (Oreochromis niloticus) Cultivation at Gerakan Pakan Ikan Mandiri Program in Kelompok Tunas Mekar Jaya, Bogor Regency - Nurul Auliya Ashshufi; Anik Martinah Hariati (Faculty of Fisheries and Marine Science, Brawijaya University, 2019)
The purpose of this study was to analyze the financial feasibility of tilapia fish farming business using the independent feed in the Tunas Mekar Jaya Group. Research location in Pamijahan Regency, Bogor Regency. Since receiving assistance, this group has produced tilapia consumption for five cycles, but the group has not recorded in detail the feasibility of the business being carried out. The method used in this research is descriptive method and method of determining respondents is the census. Data analysis methods are investment capital analysis, total production costs, total income, revenue cost ratio, profit analysis, economic profitability, net present value, internal rate of return, and payback period. From the results of data analysis, tilapia fish farming business using independent feed has an investment capital of Rp 3,596,405,000 with a total operating income of Rp 940,000,000/year, RCR 1.6 with a profit of Rp 368,587,000/year, economic profitability of 64%. NPV of Rp 33,310,800, IRR 33.31% and the rate of return on business capital in the fairly fast category, as shown by the payback period analysis for 0.12 years. The results of the financial feasibility analysis show that the tilapia fish farming program in the Independent Fish Feed Movement in the Tunas Mekar Jaya group is said to be feasible to be developed.